2009
DOI: 10.1002/ijc.24730
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging microscopy of chemotherapy‐induced apoptosis resistance in a syngenic mouse tumor model

Abstract: During cancer therapy with DNA-damaging drug-agents, the development of secondary resistance to apoptosis can be observed. In the search for novel therapeutic approaches that can be used in these cases, we monitored chemotherapyinduced apoptosis resistance in a syngenic mouse tumor model. For this, syngenic murine colorectal carcinoma cells, which stably expressed a FRET-based caspase-3 activity sensor, were introduced into animals to induce peritoneal carcinomatosis or disseminated hepatic metastases. This sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…Importantly, improving BRET sensors will require the development of brighter luminescence proteins in addition to those described above (e.g., Nanoluc; Hall et al, 2012;Stoddart et al, 2015), which are capable of energy transfer to red-shifted fluorophores. Recently, RFPs have been used in both BRET and FRET sensors in living organisms (Keese et al, 2010;Dragulescu-Andrasi et al, 2011;Bakayan et al, 2014), also for the study of a GPCR (Fruhwirth et al, 2011). A red-shifted unimolecular BRET sensor has also been successfully used to detect a cancerassociated antigen in vivo using an antibody attached to a farred fluorescent indocyanine derivative fused to Cypridina luciferase via glycol chains , illustrating the advantages of red-shifted BRET emission for in vivo detection in tissue.…”
Section: Optimization Of Ret Sensors For In Vivo Applicationsmentioning
confidence: 99%
“…Importantly, improving BRET sensors will require the development of brighter luminescence proteins in addition to those described above (e.g., Nanoluc; Hall et al, 2012;Stoddart et al, 2015), which are capable of energy transfer to red-shifted fluorophores. Recently, RFPs have been used in both BRET and FRET sensors in living organisms (Keese et al, 2010;Dragulescu-Andrasi et al, 2011;Bakayan et al, 2014), also for the study of a GPCR (Fruhwirth et al, 2011). A red-shifted unimolecular BRET sensor has also been successfully used to detect a cancerassociated antigen in vivo using an antibody attached to a farred fluorescent indocyanine derivative fused to Cypridina luciferase via glycol chains , illustrating the advantages of red-shifted BRET emission for in vivo detection in tissue.…”
Section: Optimization Of Ret Sensors For In Vivo Applicationsmentioning
confidence: 99%
“…However, as the field of FRET biosensors is still an emerging area, only a few research groups have thus far used this powerful technique in vivo. For example, FRET biosensors have been used to measure the proteolytic activity of calpain in muscles (Stockholm et al, 2005), changes in calcium concentration and myosin light-chain kinase activity in arteries (Zhang et al, 2010), and the induction of apoptosis in the skin (Bins et al, 2007), colorectal carcinomas and lymphomas (Breart et al, 2008;Keese et al, 2010). In particular, the apoptosis sensor has been of interest for tumor biology, because tumor cells have to overcome many apoptotic signals during several steps of metastasis.…”
Section: Intravital Imaging Of Proteins Proteases Signaling Pathwaymentioning
confidence: 99%
“…2C,D) (Bins et al, 2007). Keese and colleagues used FRET IVM of this biosensor to study the induction of apoptosis resistance upon chemotherapy (Keese et al, 2007;Keese et al, 2010). Moreover, Breart and colleagues used this biosensor to study apoptosis of tumor cells by cytotoxic T lymphocytes (CTLs) and showed that a CTL kills, on average, one tumor cell every 6 hours (Breart et al, 2008).…”
Section: Intravital Imaging Of Proteins Proteases Signaling Pathwaymentioning
confidence: 99%
“…In an initial study FLIM-FRET was used to image the interaction between GFP-tagged chemokine (C-X-C motif) receptor 4 (CXCR4-GFP) and red fluorescent protein (RFP)-tagged protein kinase C  (PKCA-RFP) in mammary carcinoma xenografts (Kelleher et al, 2009). In another study, FLIM was used to image a caspase-3-based FRET probe to examine the development of drug-resistance in a syngenic mouse tumor model (Keese et al, 2010). In the first case, the authors used fluorescence lifetime to demonstrate differences in receptor binding when comparing deep and shallow tumor regions.…”
Section: Fret and Flimmentioning
confidence: 99%